2015
DOI: 10.1016/j.aap.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning differentially predicts different dimensions of older drivers’ on-road safety

Abstract: The extent to which deficits in specific cognitive domains contribute to older drivers’ safety risk in complex real-world driving tasks is not well understood. We selected 148 drivers older than 70 years of age both with and without neurodegenerative diseases (Alzheimer disease-AD and Parkinson disease-PD) from an existing driving database of older adults. Participant assessments included on-road driving safety and cognitive functioning in visuospatial construction, speed of processing, memory, and executive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 53 publications
7
75
0
7
Order By: Relevance
“…Recent research has provided positive evidence for simulator validity Fisher et al, 2011;Shechtman, Classen, Awadzi, & Mann, 2009), nevertheless a validation on road is necessary to validate our conclusions that each specific driving measure is related to a specific set of functional abilities and that only a small proportion of the variability observed in specific driving measures is explained by functional abilities. Results of recent studies investigating the relation between cognitive abilities and driving errors in different situations on road seems to be in line with our results (Aksan et al, 2015;Anstey & Wood, 2011). However, future research should investigate the relation between several measures of driving ability on road (not only driving errors) with several functional abilities (not only cognitive abilities) since the results of the present study indicate that each specific driving measure is related to a specific set of functional abilities.…”
Section: Limitations and Future Researchsupporting
confidence: 92%
See 2 more Smart Citations
“…Recent research has provided positive evidence for simulator validity Fisher et al, 2011;Shechtman, Classen, Awadzi, & Mann, 2009), nevertheless a validation on road is necessary to validate our conclusions that each specific driving measure is related to a specific set of functional abilities and that only a small proportion of the variability observed in specific driving measures is explained by functional abilities. Results of recent studies investigating the relation between cognitive abilities and driving errors in different situations on road seems to be in line with our results (Aksan et al, 2015;Anstey & Wood, 2011). However, future research should investigate the relation between several measures of driving ability on road (not only driving errors) with several functional abilities (not only cognitive abilities) since the results of the present study indicate that each specific driving measure is related to a specific set of functional abilities.…”
Section: Limitations and Future Researchsupporting
confidence: 92%
“…This latter driving measure was also predicted by visual acuity. This finding, that it depends on the specific driving measure under investigation, is in line with previous studies with older drivers specifically addressing this issue (Aksan et al, 2015;Anstey & Wood, 2011;Mullen et al, 2008). For example, the UFOV predicted performance on a rural highway course, while the ANT also predicted performance on parking lot courses (Mullen et al, 2008).…”
Section: Investigating Specific Measures Of Older Drivers' Driving Absupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies show that older drivers (+75) have the highest crash rate among all the age groups (Eby et al, 1998). In addition, cognitive impairments which are likely to appear in age over 65 decline the driving safety (Aksan et al, 2015). However, the patterns of accidents vary among different groups of older people.…”
Section: Introductionmentioning
confidence: 96%
“…Generic tools and dementia screening instruments do not assess the specific deficits that cause drivers to become unsafe. A consistent body of research has demonstrated that memory deficits are not typically associated with unsafe driving (Reger et al, 2004;Anstey et al, 2005;Aksan et al, 2015), which may explain why patients with early AD may continue to drive safely. In contrast, deficits in executive function, visual selective attention, and processing speed predict crashes in older drivers (Ball et al, 2006;Dawson et al, 2010;Anstey et al, 2012).…”
Section: Cognitive Functionmentioning
confidence: 99%